Nutritional Evaluation of Short-horned Grasshopper (Oxya hyla hyla Serville) as a Substitute for Soybean Meal in Compound Diets of Rohu (Labeo rohita Hamilton) - Chaudhary, Prashant; Khanal, Dipak; Gurung, Shailesh; Bhattarai, Shiva Shankar (Agriculture Development Journal, 2024)
The growth effects of partial substitution of soybean meal for grasshopper meal (Oxya hyla hyla) in compound diets of Rohu fish (Labeo rohita) were evaluated for 75 days at the aquaculture research center in IAAS, Paklihawa Campus with 16 meshed cages of 1 m3 size, stocked with 12 fingerlings. Completely Randomized Design was used with 4 treatments and 4 replications. Treatments included the incremental substitution of Soybean meal (SM) for Grasshopper meal (GM) as 0% GM, 10% GM, 20% GM and 30% GM. Feeding rates were adjusted every month based on observed body weight. Fish parameters were observed at 16, 27, 45, 60 and 75 days after stocking, whereas, the physical water parameters were observed daily. During the study period, the recorded mean water temperature, pH, dissolved oxygen and survivorship were 19°C, 8.2, 6.4 mg/L and 64.6% respectively. Average growth rate, relative growth rate, specific growth rate, daily weight gain and protein efficiency ratio showed no significant difference (p>0.05) among the treatments. The Feed Conversion Ratio of 20% GM and 30% GM were statistically similar and superior to 0% GM and 10% GM as well. To sum up, we did not have enough evidence to prove the superiority of grasshopper meal incorporated diet on rohu, perhaps because of a lower feed efficiency.